2019
DOI: 10.4236/jsbs.2019.92006
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency of Briquettes Derived from Three Agricultural Waste’s Charcoal Using Two Organic Binders

Abstract: Waste management could contribute significantly to reducing environmental degradation. Studies showed that briquetting provides with or without binder helps to manage wastes as energy fuels. However, the properties of many binders are not investigated extensively. This work investigated the effect of two organic binders' low rate on energy efficiency of Briquettes produced from charcoals of Tender Coconut Husks (TCH), Palm Kernel Shells (PKS) and Corn Cobs (CC). Bombax Costatum calyx (B) and Cissus Repens bark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…The dried matter transformed into a pulverized form and converted to briquettes [6]. It is a real solution of protecting the environment and limiting deforestation by making briquette from biomass (waste) [7]. The biomass is not directly used, it can be converted to get the fuel with the desirable properties, i.e., the high calorific value, high durability, and low pollution emission [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dried matter transformed into a pulverized form and converted to briquettes [6]. It is a real solution of protecting the environment and limiting deforestation by making briquette from biomass (waste) [7]. The biomass is not directly used, it can be converted to get the fuel with the desirable properties, i.e., the high calorific value, high durability, and low pollution emission [8].…”
Section: Introductionmentioning
confidence: 99%
“…Briquette from biomass contributes to the energy mix. The advantage of transforming biomass has highly efficient, and now it becomes research interest [7]. It seems that using the waste in briquettes will reduce some of the waste problem and increase national energy needs [9].…”
Section: Introductionmentioning
confidence: 99%
“…According to Xiao et al [79], increasing the usage of charred briquettes made from renewable biomass waste streams can significantly decrease deforestation and harmful gas emissions. Azasi et al [80] and Obeng et al [81] both concluded that increased usage of charcoal briquettes adds significantly to energy sufficiency and the reduction of reliance on fossil fuels in developing nations. However, variables such as cost, availability, convenience of use, quality, and education on the benefits of utilizing briquettes influence the rising usage of burned briquettes [82].…”
Section: Sawdust Briquettesmentioning
confidence: 99%
“…Several studies were focus on the energy recovery of biodegradable residues [3][4][5][6][7]. Also for the search for alternative fuels, many researchers depend on their localization have evaluated the energy potential of certain local agricultural wastes depending on their availability in the region [7][8][9][10][11][12]. Others studies were focused on the optimal carbonization of these residues and agglomeration of biomass charcoals briquettes using organic or mineral binders [13][14][15].…”
Section: Introductionmentioning
confidence: 99%